Differential and partial cross sections of elastic and inelastic positronium-helium-atom scattering - Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2000)
A three-positronium-state coupled-channel model was utilized to investigate the scattering of positronium (Ps) by a helium atom at low and medium energies. A regularized symmetric nonlocal electron-exchange model potential was utilized for this purpose. The differential cross sections for elastic scattering and target-elastic Ps excitations were calculated. The results were found to agree with the theoretical references.